2022
DOI: 10.3390/life12040492
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Approaches for Tuberculum Sellae Meningiomas: Institutional Experience in a Series of 34 Patients

Abstract: (1) Background: The aim of the present study was to evaluate our institutional outcome in tuberculum sellae meningioma (TSM) patients treated microsurgically using multiple skull base approaches, including a transcranial approach and an extended endonasal transsphenoidal approach. (2) Materials and Methods: This is a retrospective study that includes 34 patients with TSM. The study aimed to observe the efficacy of the different common approaches used by a single neurosurgeon. All the patients were evaluated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although meningiomas are more commonly found in females, the occurrence of the cystic type is more prevalent in males and children, presenting an intriguing aspect of genderbased variation in manifestation. [7][8][9][10][11] Our patient's case epitomized the complexity associated with cystic meningiomas. Her rapid neurological deterioration and worsening clinical state within minutes warranted immediate attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although meningiomas are more commonly found in females, the occurrence of the cystic type is more prevalent in males and children, presenting an intriguing aspect of genderbased variation in manifestation. [7][8][9][10][11] Our patient's case epitomized the complexity associated with cystic meningiomas. Her rapid neurological deterioration and worsening clinical state within minutes warranted immediate attention.…”
Section: Discussionmentioning
confidence: 99%
“…They demand careful consideration to avoid misdiagnosis and ensure appropriate treatment. Although meningiomas are more commonly found in females, the occurrence of the cystic type is more prevalent in males and children, presenting an intriguing aspect of gender‐based variation in manifestation 7–11 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to these benefits, this endonasal technique offers greater access across the anterior and medial walls of the CS. 39,40 Cavallo et al 341 conducted a comparative trans nasal and endoscopic transnasal approach study and, comparing different locations of CS, concluded that the endoscopic endonasal technique for CS allows for better observation and identification of surgical platforms. Anand et al 42 , also evaluated this technique and reported that it was a low-morbidity, safe alternative to medial-lateral resection of CS tumors with a variety of reconstructive choices.…”
Section: Endoscopic Endonasal Approach (Eea) To Cs Surgerymentioning
confidence: 99%
“…The size, location and grade of the tumor have a major impact on the type and severity of such impairments. They may be secondarily aggravated by sequelae of surgery, radiation, chemotherapy or secondary disease progression [ 21 , 22 ]. As patients can present with a diversity of impairments, an individualized and multidisciplinary rehabilitative approach is required.…”
Section: Introductionmentioning
confidence: 99%